Pertanggungjawaban Pidana Pelaku Tindak Pidana Penipuan Online Berdasarkan Perspektif KUHP dan Undang-Undang Informasi dan Transaksi Elektronik - Aina Aurora Mustikajati; Sulistyanta Sulistyanta (Lembaga Pengembangan Kinerja Dosen, 2024)
Cybercrime is a criminal act using computer technology which will increase in 2022 based on data from the National Police Bareskim, namely around 8,831 cases. The crime of fraud online or via electronic media, namely fraud at online social gatherings. Fraud is generally regulated in Article 378 Book II Chapter XXV of KUHP which has changed with the enactment of Undang-Undang Nomor 1 Tahun 2023 tentang Kitab Undang-Undang Hukum Pidana (or known as the KUHP Nasional) in Article 492 Chapter XXVII concerning Criminal Acts of Fraud and specifically in Article 28 paragraph (1) of concerning Undang-Undang Nomor 1 Tahun 2024 tentang Perubahan Kedua Atas Undang-Undang Nomor 11 Tahun 2008 Tentang Informasi Dan Transaksi Elektronik regarding electronic transaction fraud. This research uses normative legal research methods with a statutory approach and case studies on online social gathering fraud cases. The research results show that criminal liability in cases of online social gathering fraud according to the Information and Electronic Transactions Law must fulfill the elements of the article: setiap orang; dengan sengaja; mentransmisikan Informasi Elektronik dan/ atau Dokumen Elektronik; berisi pemberitahuan bohong atau informasi menyesatkan; yang mengakibatkan kerugian materiel bagi konsumen dalam Transaksi Elektronik. The aim of criminal law is to make the defendant realize his mistake and prevent him from repeating the crime he committed.